2021
DOI: 10.1177/03080226211008722
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cognitive function and performance in instrumental activities of daily living in older adults

Abstract: Introduction Deficits in cognition have been found to be associated with problems in performing daily activities; however, it is unknown what specific domains of cognition are related to each daily activity. Method Thirty-six occupational therapists identified the 20 most important instrumental activities of daily living for older adults and the cognitive demands required. Thirty-two older adults rated the perceived mental effort when performing these activities. They were assessed on their cognitive functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Seemingly trivial activities demand several temporally overlapping cognitive functions such as planning, problem-solving, recall, and execution [ 7 ]. Toth et al [ 8 ] demonstrated in collaboration with 36 occupational therapists that the 20 most critical instrumental ADL were closely related to different cognitive functions in older adults. Cognitive domains that have been frequently discovered in this context are memory, executive functions (EF), attention, visuospatial abilities, and language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seemingly trivial activities demand several temporally overlapping cognitive functions such as planning, problem-solving, recall, and execution [ 7 ]. Toth et al [ 8 ] demonstrated in collaboration with 36 occupational therapists that the 20 most critical instrumental ADL were closely related to different cognitive functions in older adults. Cognitive domains that have been frequently discovered in this context are memory, executive functions (EF), attention, visuospatial abilities, and language.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive domains that have been frequently discovered in this context are memory, executive functions (EF), attention, visuospatial abilities, and language. They also found that, for instance, in grocery shopping, making and keeping medical appointments and medication management EF were the most demanded cognitive domains, whereas paying bills, making a phone call, and making and keeping medical appointments were identified to require language the most [ 8 ]. In addition, there exists a correlation between ADL performance, multimorbidity, and quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment is associated with difficulties performing daily activities (Toth et al, 2021), and thus is a significant consideration in DMC assessment for IL. Occupational therapists argued that cognitive-function is best understood within the context of performing activities of daily living, as older people often compensate for deficits by utilising other skills or aids.…”
Section: Discussionmentioning
confidence: 99%
“…The daily activities were chosen based on the results of a previous study examining the most important, frequently performed, and cognitively demanding IADL completed by older adults that facilitate independent community living [ 56 ]. The 12 IADL were divided into three blocks, each containing four activities.…”
Section: Methodsmentioning
confidence: 99%